Analysis of climatic factors for the selection of greenhouse glazing materials in Ilorin, Nigeria (2011)
The effect of climate change in recent times has necessitated the need for a controlled environment for the cultivation of many crops which were hitherto cultivated under natural tropical condition. An appropriate method of accomplishing this is through the use of greenhouses which modify the environment to produce a micro-climate suitable for optimum plant growth. The successful use of greenhouses depends on the choice of appropriate glazing material. Tomatoes are precious crop demanded all year round but the production of which is being reduced by the effect of climate change. Desirous to increase the level of production, the study attempts to identify appropriate glazing material for greenhouse: for the production of tomatoes in Ilorin, Nigeria. Climatological data were collected from the Ilorin International Airport and analyzed in order to identify appropriate - covering materials for the development of greenhouse structures in Ilorin. Double layer polyethylene and white corrugated polyvinylchloride were the two glazing materials that have the lowest inner surface temperatures arid also satisfy the condition of heat load. To derive the maximum benefits of greenhouses, in addition to using these materials, Proper ventilation and shading of the greenhouses are recommended.